The Relationship Between Body Mass Index And Hand Grip Strength In Adolescents Aged 13-16 Years - Sumadewi, Komang Trisna; Adri, Nyoman Ayu Paramita; Wijaya, Putu Austin Widyasari (Universitas Muhammadiyah Surabaya, 2025)
Nutritional status is of particular concern in both developed and developing countries. The prevalence of overnutrition and obesity, especially in adolescents, continues to increase. Various parameters can be used to assess a person's physical fitness. Hand grip strength is one of the parameters used to evaluate nutritional status and physical fitness and predict various metabolic diseases. This study aims to determine the relationship between Body Mass Index (BMI) and hand grip strength in adolescents aged 13-16. The research design was analytic observation with a cross-sectional approach at SMP Negeri 7 Denpasar—sampling technique with simple random sampling of as many as 100 respondents based on inclusion and exclusion criteria. The nutritional status criteria are guided by the Indonesian Ministry of Health, namely underweight (-3SD to -2SD), normal (-2SD to +1SD), overweight (+1SD to +2SD), and obesity >+2SD. The classification of hand grip strength that we use includes Weak (< 26.6 kg), normal (26.6 kg), and strong (> 26.6 kg) for men, while for women, they are weak (< 27.1 kg), normal (27.1 kg), strong (> 27.1 kg). Data were analyzed using the Chi-Square Test. The results obtained in this study include the majority of 13-year-olds (55%), male gender (56%), weak hand grip strength (54%), and normal BMI (43%). The mean BMI was 20.49±4.24, and the mean hand grip strength was 26.74±9.33. Based on the Chi-Square test, there was a significant relationship (p<0.001) between BMI and hand grip strength. Thus, this study can conclude that a substantial relationship exists between BMI and hand grip strength in adolescents aged 13-16.